Benign monomelic amyotrophy in a 7-year-old girl with proximal upper limb involvement: case report - Yılmaz, Öznur; Alemdaroğlu, İpek; Karaduman, Ayşe; Haliloğlu, Göknur; Topaloğlu, Haluk (The Turkish Journal of Pediatrics, 2011)
Monomelic amyotrophy (MMA) is a benign motor neuron disease characterized by neurogenic amyotrophy, which usually affects one of the upper or lower extremities. Progression is slow and symptoms are clinically stable. Symptoms are seen in the second or third decades of life. In this study, we present a seven-year-old girl who was diagnosed and directed to the Physiotherapy Department at the age of 5 years and had unilateral proximal upper limb involvement. Family history of the case was recorded. Neurologic evaluation was performed. Range of joint motion, muscle shortness and strength, posture, extremity lengths, gait, timed performance, arm function, and motor and mental maturation were assessed. The physiotherapy program was designed progressively as strengthening and resistive exercises. Motor and mental developmental milestones were normal. There was no limitation in active or passive motion of all joints. She had more flexible joints, scapula alata, asymmetry between shoulder levels, and weakness on proximal muscles of the right upper extremity. In the follow-up assessment at eight months, there was no asymmetry between shoulder levels and scapular symmetry began to improve. Female gender and involvement restricted to one proximal upper limb are rare in the literature. This patient demonstrates the positive effects of physical therapy with early diagnosis of MMA. The rapid recovery of muscle weakness shows the importance of strengthening and resistive exercises applied to specific muscles in the treatment.